2013
DOI: 10.1007/s00299-013-1399-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerolipids are master players in plant hormone signal transduction

Abstract: Phosphoglycerolipids are essential structural constituents of membranes and some also have important cell signalling roles. In this review, we focus on phosphoglycerolipids that are mediators in hormone signal transduction in plants. We first describe the structures of the main signalling phosphoglycerolipids and the metabolic pathways that generate them, namely the phospholipase and lipid kinase pathways. In silico analysis of Arabidopsis transcriptome data provides evidence that the genes encoding the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 97 publications
(92 reference statements)
0
58
0
1
Order By: Relevance
“…Lipid signaling is a main constituent of hormonal regulation. 17 We showed that SA activates PI4K and phospholipase D. [18][19][20] It is not impossible that such activity might participate in counteracting the effects of the soconsidered developmental hormones. It is at least worth investigating this hypothesis.…”
Section: How Sa Induces Dwarfismmentioning
confidence: 87%
See 1 more Smart Citation
“…Lipid signaling is a main constituent of hormonal regulation. 17 We showed that SA activates PI4K and phospholipase D. [18][19][20] It is not impossible that such activity might participate in counteracting the effects of the soconsidered developmental hormones. It is at least worth investigating this hypothesis.…”
Section: How Sa Induces Dwarfismmentioning
confidence: 87%
“…Interestingly, phosphoinositide gradients were shown to be necessary for a correct polarity of PIN auxin carriers. 17,23,24 Therefore, the double mutation could lead to an alteration in phosphoinositide gradient formation, thus leading to deficient root tip growth.…”
Section: Rosette and Root Statures Are Not Necessarily Connectedmentioning
confidence: 99%
“…These second messengers then activate protein kinase C (PKC) and the ER-localised IP 3 receptor, respectively, in animal cells [1,2]. However, although the PI-PLC signaling cascade is present in plants [5][6][7], genes encoding PKC and the IP 3 receptor have not been found in terrestrial plant genomes, suggesting differences in second messenger systems between animals and plants. To date, the genomes of a variety of unicellular and multicellular algae have been sequenced [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] as shown in (Table 1).…”
mentioning
confidence: 98%
“…They have also proposed a parallel between the IP 3 and IP 6 signalling systems because these two molecules are both produced by the action of PI-PLC. Although neither an IP 3 nor an IP 6 receptor have yet been identified in terrestrial plants, it is possible that an IP 3 receptor or an IP 6 receptor of unknown structure is present in streptophytes. Taken together, comparative genomic information clearly demonstrates the loss of the IP 3 receptor gene in red algae, green algae except for Volvocales and streptophytes during plant evolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation